STUDI WAKTU DHUHA DALAM PRESPEKTIF FIQIH DAN HISAB ILMU FALAK - Abd. Karim Faiz; Agus Muchsin; Wahidin (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2020)
Abstract : Dhuha time is a special time. Allah SWT swears in the name of Dhuha time and Dhuha time becomes one of the names of surah in Al-Qur'an. This privilege is also included by Allah SWT regarding the law of taklifi for the people of Prophet Muhammad SAW to perform prayers at dhuha time (Sunnah Dhuha Prayer). The scholars of madzhab differ in their opinion in determining the time and the law. Therefore, the writer will conduct a study (study) about the time of dhuha in two perspectives, namely the perspective of madzahib fiqh and hisab of Falak Science (astronomical). The formulations of the problems in this study are: first, how is the dhuha time in the perspective of madzahib fiqh? Second, how is the time of Duha in the perspective of falak? This research is a qualitative research (Library Research). The presentation of the data in this article uses the narrative method, which describes all the findings of the research data. As for the findings in the study of this paper, first there is a mistake of opinion in the initial determination of the time for Duha prayer. Second, According to astronomical hisab the time of Duha starts 18 minutes after the time of shuruq (sunrise). Keywords : Dhuha, Fiqh, Hisab.